Chromatin Remodeling Complex NuRD in Neurodevelopment and Neurodevelopmental Disorders - Hoffmann, Anke; Spengler, Dietmar (Frontiers in Genetics, 2019)
The nucleosome remodeling and deacetylase (NuRD) complex presents one of the major chromatin remodeling complexes in mammalian cells. Here we discuss current evidence for NuRD’s role as an important epigenetic regulator of gene expression in neural stem cell (NSC) and neural progenitor cell (NPC) fate decisions in brain development. With the formation of the cerebellar and cerebral cortex, NuRD facilitates experience-dependent cerebellar plasticity and regulates additionally cerebral subtype specification and connectivity in postmitotic neurons. Consistent with these properties, genetic variation in NuRD’s subunits emerges as important risk factor in common polygenic forms of neurodevelopmental disorders (NDDs) and neurodevelopment-related psychiatric disorders such as schizophrenia (SCZ) and bipolar disorder (BD). Overall, these findings highlight the critical role of NuRD in chromatin regulation in brain development, and in mental health and disease.